EVALUATING PROFESSIONAL QUALITIES OF MEDICAL STUDENTS - Kichula, Maria; Oleksii, Kateryna; Korolova, Tetiana (Advanced Education, 2019)
Currently, the higher medical education should reflect a practical sphere of public health care as well as improvement of the quality of education of future doctors. Doctor’s activities involve almost all spheres of human life; therefore, the problem of training a highly skilled expert is urgent in the sphere of public health as doctors should have high professional and ethical expertise for more effective functioning of medicine. The research was conducted in the 2016/17 academic year at the Faculties of Medicine and Dentistry of I. Horbachevsky Ternopil State Medical University among 286 third-year and fourth-year students: 140 students of the experimental group (EG) and 146 students of the control group (CG). 24 experts (specialists in medicine) took part in the ascertaining phase of the pedagogical experiment. The special study course “Professionally important qualities of future doctors” in the EG was carried out in the form of experimental teaching while in the CG the traditional methods of teaching were used. The comparison of the results of students’ professional qualities evaluation obtained before and after the experiment allows us to state that there is a substantial increase in professionally important qualities of the EG students compared to the CG students. This paper mainly presents the idea that professional (ability to apply knowledge into practice, ability to work with a specialised literature, ability to remember a large amount of information, knowledge and use of foreign language in professional activity, adequate professional self-assessment, desire for improvement) and volitional (responsibility for the life and health of a patient, fast reaction and ability to take decisions, resistance to psychical and emotional stresses, restraint and persistence, self-control) qualities are the most important professional qualities of future doctors. Therefore, moral (attentiveness, decency, honesty, mercifulness, altruism) and social qualities (responsibility, communicative skills, tolerance, ability to build trust) are less significant for future doctors. The experimental testing of the level of professional qualities development of medical students has proved that future doctors should interpret theoretical knowledge into practical activities, constantly improving it by working with expert literature, should be able to control their emotions and react quickly in critical situations.